Sobre ser professor artista: possibilidades metodológicas para o ensinar e o fazer artístico (Revista Apotheke, 2019)
This is an account of the experiences in the class "On Being an Artist Teacher", which articulates theories and practices of arts teaching, mainly, from Dewey´s philosophical ideas. In his perspective, education is understood as an artistic (and creative) doing that opens space for the teacher-artist. Therefore, I would like to present the remarkable teaching methodology that was applied in the class, in the expectation that transgressive and active proposals such as this may stimulate new pedagogical practices and artistic processes. The discussion permeates the theoretical bases adopted in the discipline, mainly by the contemporary treatment of the invited speakers. Subsequently, the experiences of the cycle of challenges are presented, which were proposed as a way to instigate reflective thinking and research through artistic practices, as Sullivan (2005) conceives. The conception that art is also life and artistic and creative thinking are part of daily life were the main learning.
Keywords: teaching methodology; artistic doing; art